1999
DOI: 10.1007/s004399900091
|View full text |Cite
|
Sign up to set email alerts
|

CTG repeats distribution and Alu insertion polymorphism at myotonic dystrophy (DM) gene in Amhara and Oromo populations of Ethiopia

Abstract: Myotonic dystrophy (DM) is a dominantly inherited neuromuscular disease, highly variable and multisystemic, which is caused by the expansion of a CTG repeat located in the 3' untranslated region of the DMPK gene. Normal alleles show a copy number of 5-37 repeats on normal chromosomes, amplified to 50-3000 copies on DM chromosomes. The trinucleotide repeat shows a trimodal allele distribution in the majority of the examined population. The first class includes alleles carrying (CTG)5, the second class, alleles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
3
4
1
Order By: Relevance
“…Along with the North African Saharawi, the Basques and the Druze, they fall towards the other Sub‐Saharan African populations, though still within the broad western Eurasian cluster on the PC plot (Figure 2). This observation reflects previous research on the Amhara and Oromo, in which they were found to contain both elements of the African and Middle Eastern/European gene pools (Ciminelli et al 2002; De Stefano et al 2002; Gennarelli et al 1999). Furthermore, while some previous analyses have shown a statistically significant difference between the Amhara and Oromo (e.g.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Along with the North African Saharawi, the Basques and the Druze, they fall towards the other Sub‐Saharan African populations, though still within the broad western Eurasian cluster on the PC plot (Figure 2). This observation reflects previous research on the Amhara and Oromo, in which they were found to contain both elements of the African and Middle Eastern/European gene pools (Ciminelli et al 2002; De Stefano et al 2002; Gennarelli et al 1999). Furthermore, while some previous analyses have shown a statistically significant difference between the Amhara and Oromo (e.g.…”
Section: Discussionsupporting
confidence: 90%
“…Along the second component the higher frequency of B002 found in Ethiopian and Yemenite Jews, compared to the other Jewish populations, pulls them towards the Asian samples. Genetic, archaeological and cultural evidence suggests that there has been a close relationship between Ethiopia and southern Arabia, particularly Yemen (Barnavi 1992; Corbo et al 1999; Gennarelli et al 1999; Passarino et al 1998; Philipson 1993; Rosenberg et al 2001; Tartaglia et al 1996; Tishkoff et al 1998), resulting in periods of gene flow between the two regions; the X‐chromosome data presented here further supports this theory. While there has likely been very little direct gene flow between Ethiopian and Yemenite Jews, given the isolation of Ethiopian Jews as indicated by their pre‐Talmud cultural and religious practices, there has undoubtedly been direct gene flow between non‐Jewish Ethiopian and Yemenite populations, and hence indirect gene flow between the Ethiopian and Yemenite Jewish populations.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This concurs with the data that report that 68% of apparently normal relatives of our DM patients refused to undergo DNA analysis. Furthermore, our results may be an underestimation of the real prevalence of oligosymptomatic DM patients if we consider the relative stability of minimal CTG expansion in affected families [22] and a theoretical still unknown clinical shifting rate among ‘pre‐mutation’ CTG expansion states [23,24].…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, while some previous analyses have shown a statistically significant difference between the Amhara and Oromo (e.g. De Stefano et al 2002;Gennarelli et al 1999), others have failed to find such differences (e.g. Corbo et al 1999;Passarino et al 1998;Tartaglia et al 1996).…”
Section: Discussionmentioning
confidence: 89%